2005
DOI: 10.1152/japplphysiol.00647.2004
|View full text |Cite
|
Sign up to set email alerts
|

Nonsymmetrical double logistic analysis of ambulatory blood pressure recordings

Abstract: Head, Geoffrey A., Christopher M. Reid, and Elena V. Lukoshkova. Nonsymmetrical double logistic analysis of ambulatory blood pressure recordings. J Appl Physiol 98: [1511][1512][1513][1514][1515][1516][1517][1518] 2005. First published November 5, 2004; doi:10.1152/japplphysiol.00647.2004.-We developed an asymmetric double logistic curve-fitting procedure for circadian analysis that can determine the rate of change in variables during the day-to-night separately from the night-to-day transition for use in anim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
28
0
2

Year Published

2006
2006
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 21 publications
0
28
0
2
Order By: Relevance
“…Several other models were also available in the literature to describe the daily based variability of BP. Some models focused on the BP deference between daytime and nighttime BP such as the square wave fit model [27], some model focused on the transit phase between day time and night-time BP changes such as double logistic model [20,28,29]. The limitation of these models is the lack of description of the important features regarding BP fluctuations.…”
Section: Discussionmentioning
confidence: 99%
“…Several other models were also available in the literature to describe the daily based variability of BP. Some models focused on the BP deference between daytime and nighttime BP such as the square wave fit model [27], some model focused on the transit phase between day time and night-time BP changes such as double logistic model [20,28,29]. The limitation of these models is the lack of description of the important features regarding BP fluctuations.…”
Section: Discussionmentioning
confidence: 99%
“…7 Thus each parameter signifies an important characteristic of the circadian cardiovascular profile. This method can best predict the path of the blood pressure during the rising phase, independent of other times of the day, and independent of how long it takes.…”
mentioning
confidence: 99%
“…It has been suggested that this method constrains the pattern to a particular shape, but this assumption is not correct. The flexibility and independence of the parameters allows for the pattern to follow a single symmetrical cosine function, a saw tooth shape in either direction as well as a square wave-like shape (see Figure 1 of Head et al 7 ). This method, however, does not allow us to follow complex fluctuations within the plateaus as can the 4-or-moreelement Fourier method.…”
mentioning
confidence: 99%
“…Um exemplo foi documentado no Britsh Heart Journal por meio de uma carta de Gerbes, Haen e Arbogast (1985) criticando o método estatístico utilizado por Davies (DAVIES et al, 1984) A elevação da pressão arterial em uma segunda fase do ciclo claro/escuro considerada por Gerbes et al como sendo erro de coleta, pode ser considerada um padrão ultradiano desse ritmo (VEGLIO et al, 1994;RABBIA et al, 1997;SCORZONI et al, 1997;HERMIDA et al, 2002;PEREZ-LLORET et at 2004;). Como forma de avaliar esse padrão ultradiano da pressão arterial, Head (2004) propõe o método duplo-logistico como forma de medir os componentes ultradianos apresentados pela pressão arterial e frequência cardíaca (HEAD et al, 2005). Esse método consiste em seis pontos (Figura 24); P1; momento de maior valor na curva durante a fase escura.…”
Section: Discussionunclassified
“…O método duplo-logístico tem sido utilizado em uma série de estudos (HEAD et al, 2005;HEAD et al, 2006;HEAD 2010HEAD et al, 2010, nos quais os autores demonstraram ser o método mais adequado tanto para comparações rítmicas em animais quanto em humanos, não vindo a ser um método que desqualifique o Cosinor, mas possivelmente o complemente (HEAD et al 2004;KATZ et al, 2012).…”
Section: Discussionunclassified